Brunei: From the Age of Commerce to the 21st Century, Marie-Sybille de Vienne. Singapore: NUS Press, 2015, 384 pages. ISBN: 978-9971-69-818-8 - Ooi Keat Gin, (Kajian Malaysia, 2015)
The cover image says it all: Sultan Hassanal Bolkiah of Brunei looking regal and resplendent in black tunic with yellow sash bedecked with an array of medals on a motorcade on the occasion of his 59th birthday on 15 July 2005 against the backdrop of the iconic Sultan Omar Ali Saifuddin Mosque. Here one witnessed a contemporary Malay Muslim monarch ceremoniously sheltered by the yellow umbrella with the golden dome of a mosque as background altogether representing and symbolising the national concept of Melayu Islam Beraja (MIB) (Malay Islamic Monarchy). It has been a while since the appearance of a booklength work of this small Malay Muslim absolute monarchic state that straddled on the northeast coast of the island of Borneo like twin teardrops